Students’ perceptions of English teachers’ use of learning materials during the COVID-19 pandemic - Nirmala; Baso Jabu; Chairil Anwar Korompot (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
Students' perceptions of learning tools used by English teachers during the COVID-19 pandemic. Students' perceptions of the learning tools used by English teachers during the COVID-19 pandemic can be categorised into five areas, namely the enjoyment of learning English, the ability to provide students with feedback on the learning tools, the planning of online learning, the assessment of online learning and the limitations of online learning. The researcher used both quantitative and qualitative methods to achieve the research objectives. Data collection was in the form of Likert questionnaires and Google Forms interviews. The population of the study was students in the English programme in 2020. The questionnaire was sent out to 40 students and the interviews were conducted by 4 students who were selected using a purposive sampling technique. The results of the data analysis showed that (1) students' perceptions of the teaching materials used by teachers in English classes during the COVID-19 pandemic were neutral, and no students perceived the teaching materials as bad or very bad; (2) students' perceptions of the teaching materials used by teachers in English classes during the COVID-19 pandemic were valid.